Inactivation Methods for Experimental Nipah Virus Infection - Lina Widerspick; Cecilia Alejandra Vázquez; Linda Niemetz; Michelle Heung; Catherine Olal; András Bencsik; Christoph Henkel; Anneke Pfister; Jesús Emanuel Brunetti; Indre Kucinskaite-Kodze; Philip Lawrence; César Muñoz Fontela; et al. (Viruses, 2022)
Nipah virus (NiV) is an emerging zoonotic paramyxovirus that causes severe disease in humans and livestock. Due to its high pathogenicity in humans and the lack of available vaccines and therapeutics, NiV needs to be handled in biosafety level 4 (BSL-4) laboratories. Safe inactivation of samples containing NiV is thus necessary to allow further processing in lower containment areas. To date, there is only limited information available on NiV inactivation methods validated by BSL-4 facilities that can be used as a reference. Here, we compare some of the most common inactivation methods in order to evaluate their efficacy at inactivating NiV in infected cells, supernatants and organs. Thus, several physical and chemical inactivation methods, and combinations thereof, were assessed. Viral replication was monitored for 3 weeks and NiV presence was assessed by RT-qPCR, plaque assay and indirect immunofluorescence. A total of nineteen methods were shown to reduce NiV infectious particles in cells, supernatants and organs to undetectable levels. Therefore, we provide a list of methods for the safe and efficient inactivation of NiV.